Nutrition and mental health [ - Leyse-Wallace, Ruth (CRC Press, 2013)
Although primary advanced vitamin and mineral deficiencies are rare in the developed world, many common health conditions deplete nutritional status, including sub-optimal dietary intake, frequent alcohol consumption, changes in appetite due to aging, food allergies or sensitivities, special diets, and eating disorders. Covering topics as diverse as aging, the brain, eating habits, genetics, lifestyle, nutrients, and psychology, this book brings together two extremely complex aspects of life-human nutrition and mental health. Organized by mental health concern as well as nutrient group, Nutrit